ANALISIS YURIDIS TERHADAP EFEKTIVITAS WILAYAH KERJA PPAT SATU PROVINSI DAN WILAYAH JABATAN NOTARIS SATU PROVINSI (STUDI NOTARIS/PPAT KOTA MEDAN) - HUSNA IFFAH AFRIDA (jurnal.unprimdn.ac.id, 2021)
Work area of PPAT (Land Deed Making Officials) is regulated in Article 12 of Government Regulation No. 24 of 2016 concerning Regulation of the Position of Land Deed Making Officials that the work area of PPAT is within a region of a province but in reality this regulation is not effectively applied. Meanwhile work area of Notary is in the entire province, but a Notary is not authorized to carry out work consecutively outside of his domicile. The problems of this research are to discuss the management of work area of PPAT and Notary in the same city, the authority and the effectiveness between PPAT that has work area and Notary that has office area in a province. This is a juridical normative research that is gained from library books with analytical descriptive type, namely to gain detail and systematical description in regards to the problems. Data is collected through Library Research using library study and interview; analyzed with qualitative method. The research concludes that the work area of PPAT has been extended to Provincial area but it has not been applied as it should due to the barriers qf inaccessible online system in the Province. Notary has office area that covers the entire Province from his domicile. Nevertheless, a Notary is not authorised to carry out the work consecutively because the position of each Notary is defined so they are able to manage their office well. Authority ofa PPAT that has work area is not the same with a Notary that has office area. The authority of PPAT is regulated by Government Regulation meanwhile the authority of Notary is regulated by the Law. The regulation for the effectiveness ofwork area ofPPAT in a Province should be applied because it opens up the opportunity for PPAT to a wider working coverage. The position of Notary and PPAT is embedded so the authorities should be synergized; hence, the work area should be the same so that PPAT and Notary are able to exercise their authorities more efficient.